Steerable Higher-order Mode Dielectric Resonator Antenna with Parasitic Elements for 5G Applications - Shahadan, Nor Hidayu; Jamaluddin, Mohd Haizal; Kamarudin, Muhammad Ramlee; Yamada, Yoshihide; Khalily, Mohsen; Jusoh, Muzammil; Dahlan, Samsul Haimi (IEEE, 2017)
This paper presents the findings of a steerable higher-order mode (TEy 1δ3) dielectric resonator antenna with parasitic elements. The beam steering was successfully achieved by switching the termination capacitor on the parasitic element. In this light, all of the dielectric resonator antennas (DRAs) have the same dielectric permittivity similar to that of 10 and was excited by a 50Ω microstrip with a narrow aperture. The effect of the mutual coupling on the radiation pattern and the reflection coefficient, as well as the array factor were investigated clearly using MATLAB ver. 2014b and ANSYS HFSS ver. 16. As the result, the antenna beam of the proposed DRA array managed to steer from -32° to +32° at 15 GHz. Furthermore, the measured antenna array showed the maximum gain of 9.25 dBi and the reflection coefficients which are less than -10 dB with the bandwidth more than 1.3 GHz, which is viewed as desirable for Device-to-Device communication (D2D) in 5G Internet of Things (IoT) applications.
© 2017 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other users, including reprinting/ republishing this material for advertising or promotional purposes, creating new collective works for resale or redistribution to servers or lists, or reuse of any copyrighted components of this work in other works.